Ukraine : The Cost of Weak Institutions - Tiffin, Andrew (IMF Working Papers; Working Paper ;, 2006)
Ukraine has the potential to be a very wealthy country. It has a well-educated workforce, some of the best agricultural land in the world, an enviable supply of hydrocarbons and minerals, and a relatively well-developed infrastructure. Despite these advantages, however, Ukraine's per capita income remains low. Using a cross-country stochastic-frontier framework, this paper argues that Ukraine's failure to tap its full potential is mainly a result of its market-unfriendly institutional base. With an inherited Soviet framework that is ill suited to the needs of a market economy, Ukraine has been slow to establish the institutions needed to use its resources efficiently. The paper provides a quantitative guide to the benefits, in terms of potential output, of further structural reform. Looking forward, the study finds that durable growth in Ukraine will depend primarily on the authorities' ability to implement their ambitious reform agenda, and thereby to help secure the basic foundations of a modern market economy.